Children Street Work in San José, Costa Rica, 1953-1978 - Izquierdo Vázquez, Carlos (2020)
This paper seeks to analyze the discourses in the written press about child labor on the public roads of San José, within the framework of urban expansion. It demonstrates that men predominated, the sale of various services and the classification of children from various job categories, which simultaneosly, served to judge them morally. Although their labor discipline was generally legitimized, there were also criticisms of their leisure activities, their public behaviors and their transgressions. It was considered that many of these children could fall into vagrancy and begging. Key words: Poverty, urban space, childhood, t